The role of women in the integration of immigrants. - Moussourou, Loukia M. (The Greek Review of Social Research, 2007)
<div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 378.215px; transform: rotate(0deg) scale(0.956391, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.7190269756317">The integration of women immigrants and their role in the integration process depends <div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 397.633px; transform: rotate(0deg) scale(0.986679, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.6992269744873">greatly on their “willingness” to migrate, on whether or not they are in the receiving <div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 417.052px; transform: rotate(0deg) scale(0.97223, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.76786697845466">country with their children, on whether they intent to stay temporarily or indefinitely, <div style="font-size: 13.4949px; font-family: serif; left: 111.785px; top: 436.471px; transform: rotate(0deg) scale(1.07481, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="467.54402702331544">on the closeness of their relationships with relatives and friends back home – <div style="font-size: 13.4949px; font-family: serif; left: 111.785px; top: 455.889px; transform: rotate(0deg) scale(0.957234, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="161.038689307785">particularly with their mother.